Mississippi River safeguarding landscapes: battures, levées and marshlands - Minguito García, Ana Patricia (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2024)
The battures, levees, and marshlands that outline the Mississippi River winding banks, built a linear peri-urban landscape as a dam. Their historical construction process, marked by major overflows and floods, configures an unusual symbiotic management model between two seemingly opposing pressure groups: the capricious indeterminacy of the river basin and the forceful human settlements. This unconsolidated spatial condition, reveals its capacity of indefiniteness and constant transformation to give solvency to the surrounding meteorological inclemencies and the rural-urban activity requirements. Through the analysis of three dynamic approaches, the buffering interface function played by this interstitial space as a mediating mechanism, is understood. Through various local regeneration and awareness initiatives, a tripartite unit is configured, where the joining together of battures, levées and wetlands sews the territory facing the river with the urban-rural neighborhoods. As a result, this unique landscape reality achieves a positive co-existence between nature and anthropization.
Keywords: dam; anthropization; mediating interface; environmental reconciliation; periurban landscape; symbiotic landscape